The concept of the environment within the framework of national legislations and international conventions - Toumi, Hamdoun (The International tax journal, 2025)
The corporation company is an up to date sort of commercial company which is inserted into the Algerian law with the sake of promoting the ventures and start-up foundations. These companies are characterised by resilience in dealing with procedures and facileness of establishment compared to the traditional corporation ones. According to the law no: 09/22, which comprises the commercial code, the Algerian legislation has added the simple corporation company as a new sort as a kind of economic reforms which the Algerian state witnessed. Also, as push for supporting the start-up foundations inside the commercial and financial center.